Pendampingan Pemantauan Pertumbuhan Melalui Pengukuran Status Gizi Anak Sekolah Dasar - Pomatahu, Aisah R; Pauweni, Mirdayani; Syam, Asry; Ikhsan, Haerul (Universitas Negeri Gorontalo, 2023)
Elementary school-age children range in age from 6-12. This age is the second most rapid growth period after toddlerhood. One reference to child growth is physical changes which are also often used as indicators for the nutritional status of individuals and populations. This activity aims to monitor the growth of elementary school children, and help teachers provide secondary data for schools. The target subjects were 35 children. Based on the results, it was found that there were no children with obese nutritional status, and there were 88.57% wasting, and 2.85% fat.